The issue of the impact of the ideology of marxism on the creation of a culture of daily life of the totalitarian type (for views of F. Engels) - Селевко, В. Б. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Relevance of the topic due to the redefinition of socialism in the contemporary cultural space. Conducted sociocultural analysis of ideas and views F. Engels on the nature of the Organization of everyday life, on the basis of his ideological beliefs. Attention was paid to the violent, forced perspective on day-to-day thinker sphere. It is revealed that the theorists of socialism ideas and principles formed the basis for the formation of a special type of everyday culture of the era of socialism is totalitarian.